(untitled) (Revista Apotheke, 2025)
This article aims to present and discuss some specific aspects of Dewey’s concept of aesthetic experience, highlighting it as an element present in any experience and, based on this specific aspect, drawing a parallel between the continuity and presence of this aesthetic element and teaching practice. This is a bibliographical research in which the primary source is the book Art as Experience by John Dewey. In order to achieve our objectives, we divided the text into two sections. In the first section, we present Dewey’s concept of experience and, in the second section, we proposed to establish a relationship between the characteristics of the experience (continuity, emotion, aesthetic element and consummation) and teaching practice. We concluded that the active role between spectator and artist is repeated in the relationship between teacher and student, since both the teacher and the student play an active role in the presentation, creation and recreation of the content in the class and this creation and recreation are from the classroom experience.